View of the extant plinth of the southern shrine - Temples of India Project Team (Jio Institute, 2024)
This is a view of the extant plinth of the southern shrine as seen from the south-facing elevation of the Neelkanth Mahadev Temple. The pattern of the kumbha (pot) is similar to other wall projections. The central kumbha corresponding to the main bhadra (central projection) of the temple has a depiction of Ganesha.